2021
DOI: 10.3389/fmars.2021.688316
|View full text |Cite
|
Sign up to set email alerts
|

Species That Fly at a Higher Game: Patterns of Deep–Water Emergence Along the Chilean Coast, Including a Global Review of the Phenomenon

Abstract: Deep-water emergence (DWE) is the phenomenon where marine species normally found at great depths (i.e., below 200 m), can be found locally occurring in significantly shallower depths (i.e., euphotic zone, usually shallower than 50 m). Although this phenomenon has been previously mentioned and deep-water emergent species have been described from the fjord regions of North America, Scandinavia, and New Zealand, local or global hypotheses to explain this phenomenon have rarely been tested. This publication includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 87 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Riemann-Zürneck & Gallardo (1990) inferred that the marginal ruff may have an adaptive value in this sense, favouring gas exchange in time spans of oxygen deficiency. As these episodes – usually linked to the expansion of the oxygen minimum zone – become more intense and shallower in depth due to climate change (Bakun et al ., 2015; Valdés et al ., 2021), more and more individuals may likely disperse towards the coast (see Häussermann et al ., 2021); which, not only raises new questions about their potential impact on shallow-water ecosystems, but also presents O. coliumensis as a suitable bioindicator of eutrophicated sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Riemann-Zürneck & Gallardo (1990) inferred that the marginal ruff may have an adaptive value in this sense, favouring gas exchange in time spans of oxygen deficiency. As these episodes – usually linked to the expansion of the oxygen minimum zone – become more intense and shallower in depth due to climate change (Bakun et al ., 2015; Valdés et al ., 2021), more and more individuals may likely disperse towards the coast (see Häussermann et al ., 2021); which, not only raises new questions about their potential impact on shallow-water ecosystems, but also presents O. coliumensis as a suitable bioindicator of eutrophicated sediments.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is observed along the Chilean coasts, though it is reversed in the Patagonian region: the data analysed here show that the highest species diversity occurs in the Magellanic Province (i.e., Chilean Patagonia) rather than further north (see Figure 5). Häussermann et al (2021), who have led numerous SCUBA diving expeditions of this province over the past two decades, reported that Northern Patagonia harbours the highest diversity of shallow-water anthozoans, followed closely by Central Patagonia; by comparison, Southern Patagonia harbours a lower level of biodiversity (Häussermann et al 2021). It is worth mentioning that the results reported here may be mainly reflecting the asymmetrical sampling effort of past research expeditions of Chilean coastal and marine waters and not the real pattern of coral distribution and biodiversity in this vast area.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by our study of coral species occurrence, the coastal and marine waters of Chile, a vast area comprised several biogeographic provinces and ecoregions, remain poorly explored. This area includes relevant endemic biodiversity hotspots and fragile habitats (see e.g., Häussermann et al 2021 for the continental shelf, slope, and fjord areas, and Wagner et al 2021 for the Nazca and Salas y Gómez ridges), for which biodiversity estimates are especially important. Our study also demonstrates that the largest efforts to inventory coral species of this region were made by the Challenger (1872-1876), the Lund University Chile (1948)(1949), and the Huinay Fjord (2005-2019) expeditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations